Limited Exchange Transfusion Can Be Very Beneficial in Sickle Cell Anemia with Acute Chest Syndrome: A Case Report from Tanzania - Clara Chamba; Hamisa Iddy; Erius Tebuka; Furahini Tluway; Elisha Osati; Neema Budodi; Collins Meda; Mbonea Yonazi; Anna Schuh; Lucio Luzzatto; Julie Makani (Case Reports in Hematology)
Acute chest syndrome (ACS) is a life-threatening complication of sickle cell disease (SCD) with blood transfusion an integral part in its management. Red cell exchange (RCE) transfusion is usually regarded as preferable to top-up transfusion, because it reduces the proportion of Hemoglobin (Hb) S while at the same time avoiding circulatory overload. Despite its obvious benefits, RCE is underutilized, particularly in low-resource settings which may be due to scarcity of blood products and of expertise in carrying out exchange transfusion. We report on a young woman with SCD with severe ACS who responded promptly and dramatically to a RCE of only 0.95 L (instead of the recommended 1.4 L) and had in the end an HbS level of 48% (instead of the recommended level below 30%). Limited RCE resulted in significant clinical improvement. We suggest that limited RCE may be of benefit than no RCE in SCD patients with ACS, particularly in settings where RCE is not available.